2007
DOI: 10.1128/aem.01034-07
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium Genotypes in Wildlife from a New York Watershed

Abstract: To identify the animal sources for Cryptosporidium contamination, we genotyped Cryptosporidium spp. in wildlife from the watershed of the New York City drinking water supply, using a small-subunit rRNA genebased PCR-restriction fragment length polymorphism analysis and DNA sequencing. A total of 541 specimens from 38 species of wildlife were analyzed. One hundred and eleven (20.5%) of the wildlife specimens were PCR positive. Altogether, 21 Cryptosporidium genotypes were found in wildlife samples, 11 of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 27 publications
10
153
2
2
Order By: Relevance
“…Isolate W971 was homologous with genotype W13 found in storm water, which, in turn, is the skunk genotype (6). Initially, the BLAST search for isolate W6863 erroneously indicated C. parvum as the most probable identity at the SSU rRNA gene, but this was due to the short length (484 bp) of the only horse genotype sequence available (AY273770) for comparison.…”
Section: The Studymentioning
confidence: 99%
“…Isolate W971 was homologous with genotype W13 found in storm water, which, in turn, is the skunk genotype (6). Initially, the BLAST search for isolate W6863 erroneously indicated C. parvum as the most probable identity at the SSU rRNA gene, but this was due to the short length (484 bp) of the only horse genotype sequence available (AY273770) for comparison.…”
Section: The Studymentioning
confidence: 99%
“…New York, USA, have been given temporary sequential genotype numbers prefixed by the letter W (water) until a host is identified (Feng et al 2007). …”
Section: Colleagues In Watersheds Inmentioning
confidence: 99%
“…UK E4 was most similar to but distinct from the fox genotype, and was found in a stream beside property 7; UK E6 was most similar to but distinct from Cryptosporidium canis and was Figure 1 | Phylogenetic relationships among Cryptosporidium isolates from this study and known species and genotypes reported on GenBank, as inferred by neighbour-joining analysis. Water genotype names are given in brackets after their animal hosts, according to Feng et al 2007. Numbers on branch nodes are bootstrap values (.50%) obtained from 1000 re-samples.…”
Section: Cryptosporidium Speciesmentioning
confidence: 99%
See 2 more Smart Citations